PENGEMBANGAN E-MODUL MATERI FLUIDA DINAMIS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA KELAS XI - Pynka Marsha Nikita; Albertus Djoko Lesmono; Alex Harijanto (FKIP Universitas Jember, 2018)
Abstract This study focused on the development of product learning with Dynamic FluidE-Module. This was research intended to know the validity, improve students'critical thinking skill, and to know the student's response in using the DynamicFluid E-Module. The research was conducted in SMA Negeri 4 Jember in thestudents of class XI odd semester of academic year 2016/2017. The dynamicfluid material content module packed in e-module (electronic module). Thedevelopment model used is 4D developed by Thiagarajan namely: define(definition stage), design (planning stage), development (development stage),and dissemination (dispersion stage. The average value of validity is 4.11included in the valid criteria. N-Gain obtained 0.81 with high category. Theaverage percentage of student responses was 91.81% very positive category.Dynamic Fluid E-Module can be concluded the development and posible to use.Keywords : dynamic fluid, e-module, critical thinking skill.